5b+c-43b-2c+1=1-38b-c
Chat with our AI personalities
here is how you go about solving it first write down the question 3b+4+5b-1 then change arrangement so that it looks like this 3b+5b+4-1 then solve 8b+3
4a - 5b = 74a +5b = 17From the first equation:4a = 7 + 5bsubstitute this value in the second equation:7 + 5b + 5b = 177 + 10b = 1710b = 10b = 1Now,solve for a :4a - 5(1) = 74a = 7 + 54a = 12a = 3
b-squared plus 5b plus 1 is an expression: not an equation or inequality. There is, therefore, nothing that can be solved. Second, the expression does not have real factors. It makes no sense to use product (factor) and sum to find complex factors. Using the quadratic formula or completing the squares are far simpler.
b+b+b+b+b is equal to 5b. That is because there are five b's being added up. 1+1+1+1+1 is 5 because there are five 1's being added up.
2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1